Applying the Water Governance Framework on Rural Water Development Projects in Guatemala - (:unkn) unknown (My University, 2016)
According to the Organization for Economic Cooperation and Development (OECD), ‘Water crisis is mainly a governance crisis’, (OECD, 2013). Many water experts, as individuals, organizations and even governmental bodies have developed water governance frameworks to overcome water challenges on local, national, and international levels such as Integrated Water Resource Management. In rural areas, especially in developing countries, access to safe drinking water is a daily challenge due to a variety of political, economic, and social constraints. For in-stance, some developing countries have a strong centralized governance system. Due to lack of capacity and resources, central governments are incapable of providing water services to com-munities in rural areas located farther from amenities. At the same time, decentralization, as an alternative governance framework, does not guarantee meeting the needs of rural communities. The devolution of power from central government to local authority requires individuals who have the requisite information and the incentives as well as the capacity to bear responsibility for the political and economic consequences of their decisions. Furthermore, local authorities may face the threat of being controlled and overthrown by local elite groups who could exploit the power to achieve personal goals. In 2011, OECD developed a water governance framework (WGF) to better manage the water sector and evaluate gaps within water governance mainly on governmental levels. These include measuring the policy gap, accountability gap, funding gap, information gap, administra-tive gap, objective gap, and capacity gap. The WGF has been applied in many different regions across the globe in national and sub-national levels of governments. In 2015, OECD updated the WGF based on feedback obtained from various organizations that used the framework. This study applies the OECD WGF to water projects completed in Guatemala by the Stu-dent Chapter of Engineers Without Borders at the University of Wisconsin-Milwaukee (EWB@UWM). This work represents a reciprocal testing of the WGF as well as water develop-ment projects in Guatemala. The reciprocal testing investigates the validity of applying this par-ticular water governance framework on small scale community-based water projects. In other words, this study aims to test the applicability of the WGF on rural development projects and determine strengths and weaknesses of the framework. On the other hand, this study explores the ability of rural communities to effectively utilize the WGF to identify their water policy gaps. In addition to the main anticipated outcomes that are mentioned above, the merit of this study is to help external groups, such as EWB@UWM, apply the WGF to evaluate their com-pleted water projects that are installed in rural areas. Moreover, it helps local in-country partners (individuals and organizations), as well as communities to better utilize the framework, measure the gaps in their local capacity, and communicate their needs in order that their future is sustain-able. In January 2016, site visits took place to five out of the seven projects that are being ana-lyzed. Additionally, interviews were conducted with the cofounder of EWB@UWM, Dr. Marissa Jablonski, as well as the head of EWB@UWM’s in-country partner, La Asociación de Comités Comunitarios Medio Ambiental de la Región Ixil (ACCMARI), Mr. Diego Ramirez. The outcome of the site visits and the interviews are used to identify water policy gaps in the water projects of Guatemala. More specifically, the OECD WGF addresses seven different gaps which are based on 12 principles. The site visits and interviews indicated that four out of 12 principles cannot be applied on the water systems. Therefore, these four principles are eliminated from the analysis. Hence, eight variables are identified to investigate any gaps present in the completed pro-jects. Each principle is measured through a set of questions which examines that particular prin-ciple. Each question is rated with a score from 0-10, whereas the score of a certain principle is the average score of all answers. If a principle has a score of less than ‘5’, then a water policy gap is present. The administrative gap is eliminated from the analysis because it does not apply to the water systems being analyzed. The other six WGF gaps are assigned to the eight principles that were discussed in section 7.3. Four gaps are assigned to one specific principle whereas the other two gaps, each one of them is assigned to two principles. The structure of this paper starts with a brief introduction, followed by chapter 2 that il-lustrates the specification of the project (statement of problem, statement of significance, antici-pated outcome, and research questions). Later on, extensive literature review is presented which discusses rural development works and focuses on political and economic variables. After that, the paper presents the methodology used to conduct this research, the analysis and discussion sections, ending with a set of policy implications and guidelines regarding the communities as well as the OECD WGF.
Keywords: Development; Framework; Governance; Guatemala; Rural; Water